Potential Role of Metabolic Intervention in the Management of Advanced Differentiated Thyroid Cancer - Tella, Sri Harsha; Kommalapati, Anuhya; Esquivel, Mary Angelynne; Correa, Ricardo (Frontiers in Oncology, 2017)
Well-differentiated thyroid carcinoma (DTC) is the most common endocrine malignancy that has an excellent prognosis with a 5-year survival rate of about 98%. However, approximately 50% of the patients with DTC who present with distant metastases (advanced DTC) die from the disease within 5 years of initial diagnosis even after getting the appropriate therapy. Apart from recent advancements in chemotherapy agents, the potential role of metabolic interventions, including the use of metformin, ketogenic diet, and high-dose vitamin C in the management of advanced cancers have been investigated as a less toxic co-adjuvant therapies. The role of vitamin C has been of interest again after a preclinical mice study showed that high-dose vitamin C is selectively lethal to KRAS and BRAF mutant colorectal cancer cells by targeting the glutathione pathway. This raises the possibility of utilizing high-doses of vitamin C in the treatment of aDTC where KRAS and BRAF mutations are common. Similarly, alteration of cellular metabolism by low-carbohydrate ketogenic diets can be an important therapeutic strategy to selectively kill cancer cells that mainly survive on glycolysis. Among the potential adjuvant therapies proposed in this paper, metformin is the only agent that has shown benefit in human model of aDTC, the others have shown benefit but in preclinical/animal studies only and need to be further evaluated in large clinical trials. In conclusion, in addition to concurrent chemotherapy options, these metabolic interventions may have a great potential as co-adjuvant therapy in the management of aDTC.